Fill in the blanks to explain what needs to be done in the current step to get to the next step.
3x+4−2x+9=17−x
3
�
+
4
−
2
�
+
9
=
17
−
�
Step 1: 3x+4−2x+9=17−x
3
�
+
4
−
2
�
+
9
=
17
−
�
Step 2: x+13= 17−x
�
+
13
=
17
−
�
Step 3: x+x+13=17−x+x
�
+
�
+
13
=
17
−
�
+
�
Step 4: 2x +13 = 17
2
�
+
13
=
17
Step 5: 2x+13−13=17−13
2
�
+
13
−
13
=
17
−
13
Step 6: 2x=4
2
�
=
4
Step 7: x = 2
�
=
2
2 answers
The first step is to simplify both sides of the equation by combining like terms. The second step is to isolate the variable terms on one side of the equation by adding or subtracting terms from both sides. The third step is to combine like terms again. The fourth step is to isolate the variable by further simplifying the equation. The fifth step is to simplify both sides of the equation by combining like terms. The sixth step is to isolate the variable term by dividing both sides of the equation by the coefficient of the variable. The seventh step is to simplify and find the solution for the variable.
S
e
e
h
o
w
a
n
n
o
y
i
n
g
v
e
r
t
i
c
a
l
t
e
x
t
i
s
?
e
e
h
o
w
a
n
n
o
y
i
n
g
v
e
r
t
i
c
a
l
t
e
x
t
i
s
?